MICROSURGICAL CLIPPING IN THE RUPTURED AN ANEURYSM OF ANTERIOR COMMUNICATING ARTERY: A CASE REPORT - Niryana, Wayan; Pagehgiri, Aslesa Wangpathi; Widyadharma, Putu Eka (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Ruptured saccular aneurysms are a common and serious medical problem. The prevalence of aneurysms is low during the first two decades of life and increases steadily after the third decade. Anterior communicating artery (AComA) aneurysms are regarded as the most complex of all intracranial aneurysms. Methods: Here, we report a case of an aneurysm of AComA patient with the development of microsurgical technique and intraoperative monitoring technique. Results: Permanent clipping was successfully performed in the neck of an aneurysm of AComA. Conclusion: Microsurgical clipping still remains a definitive treatment of ruptured cerebral aneurysms.